A aplicação extraterritorial dos tratados de direitos humanos no espaço marinho - Felix, Mayna Cavalcante (2019)
The present work aimed at analyzing the different jurisdictional allocation criteria in international jurisprudence, doctrine and legislation, with the purpose of examining the situations of extension of state jurisdiction, beyond the territorial limits, generating the extraterritorial application of the instruments that verse about rights humans. The regulation brought by the United Nations Convention on the Law of the Sea sometimes causes the overlapping of jurisdictions, and the applicable law must be analyzed on a case-by-case basis. This issue has been addressed in international courts through the use of effective and personal control criteria. Although, because of the special nature of the marine environment, these have proved insufficient to guarantee maximum effectiveness in the protection of human rights. In this sense, the work investigates instruments of domestic law that have been used for the extraterritorial safeguard of individuals, as well as how the public and private entities would be held accountable, in the face of human rights abuses. To this end, the first chapter dealt with the definition of the concept of jurisdiction in the area of human rights, while discussing public and private responsibilities within its jurisdictional scope. In the second chapter, the jurisdictional criteria of the law of the sea were explored, as well as the overlap of jurisdictions. In the third and last chapter, it was discussed the situations in which the extraterritorial extension of the jurisdiction will take place. It was concluded that a broad interpretation of the judicial concept should be applied, in the face of human rights violations, in order to grant it maximum protection and reduce impunity.